Making fashion more sustainable : the case of slow fashion and luxury fashion - Jussub, Khatija Imtiaz (2020)
The fashion industry is known to be one of the most wasteful industries in the world. The irresponsible over-exploitation of natural resources throughout the supply chain of companies and high consumerism levels are leading to huge environmental and social issues. This study aims to comprehend how fashion brands are responding to these pressures and how they can reconcile fashion with sustainability. To answer my research question, I draw on the business model canvas lens by analysing six of the nine components and adopted a qualitative approach. A multiple case study was conducted on two Portuguese small companies that have adopted sustainable practices. One is positioned in the luxury segment and the other in the slow fashion segment. Findings from the cases demonstrate that to reconcile fashion with sustainability all of the business canvas model blocks must incorporate sustainability as a main strategy and not as an adjacent strategy. Other strategies involve, focusing on sustainable production by selecting and using the right materials, solidifying a relationship with suppliers that share the same vision as the brand. Most importantly educate consumers on sustainable consumption and be as transparent as possible throughout all processes of manufacturing.